Reconstruction of National Agrarian Data Security through Blockchain Technology: An Urgency Following the PDNS 2 Ransomware Incident (Indonesian Journal of Agrarian Law, 2026)
The digital transformation of land administration in Indonesia, characterized by the implementation of electronic land certificates under Minister of ATR/BPN Regulation Number 1 of 2021, faces serious challenges in cyber security. The use of a centralized database system has proven to have a fatal single point of failure, as evidenced by the Ransomware attack on the Temporary National Data Center (PDNS) 2 in 2024 which paralyzed 282 government institutions, as well as the leakage of 1.3 billion data by the hacker Bjorka in 2022. This research aims to analyze the vulnerability of the current land data infrastructure and examine the urgency of adopting Blockchain technology as a land data protection solution. Using a normative legal research method with a statutory, conceptual, and case approach, the results indicate that the centralized system is no longer adequate to guarantee the integrity of national agrarian data amidst destructive cyber threats. Blockchain technology offers decentralization and immutability that can prevent data manipulation by "digital land mafias" through a transparent network consensus mechanism. The successful implementation of Blockchain in land registration in Georgia since 2016 provides empirical evidence that this technology can ensure the permanent integrity of land ownership history. Regulatory reconstruction accommodating distributed ledger technology in national agrarian law is a necessity to achieve absolute legal certainty for landholders in the digital age. This research recommends the establishment of Government Regulation-level regulations governing Blockchain technical standards, synchronization between regulations, and a pilot project in several land offices before national implementation.